(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Social networks have gained great importance today and within the formal curriculum there is generally no specific place where they are. That is why this paper seeks to see the possibilities of building peace with the analysis of violent discourses in social networks through the systematization of the union experience between the school seedbed Empowerment in Networks and the seedbed of the Antonio University Nariño, Alternative Pedagogies in order to reflect on the educational practices that lead to peace scenarios. The methodology used is the systematization of experiences from which what happened is critically interpreted and learning is identified. It is found that there is a great relationship between daily life and the use of social networks and that reflections on the violence that exists in social networks are necessary, our responsibility to be in them and the possibilities of this experience to build peace.